2015
DOI: 10.1007/s00170-015-7584-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface integrity and removal mechanism of chemical mechanical grinding of silicon wafers using a newly developed wheel

Abstract: A chemical mechanical grinding (CMG) wheel was developed for planarization of silicon wafers, which consists of magnesium oxide (MgO) abrasives and calcium carbonate (CaCO 3 ) additives, mixed with 25 % weight percentage of magnesium chloride (MgCl 2 ) solution. It was shown that chemical reactions occurred during the grinding process, which formed a softened layer on the top of silicon substrate. The reactants could be much more easily removed by mechanical abrasion than the removal of Si phase itself. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was found that there is still grinding traces on the surface of nano grinding, but the surface of CMG is smooth without grinding traces and surface damage. Dong et al [31] used a CMG wheel of magnesium oxide (MgO) abrasives to grind silicon wafers.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that there is still grinding traces on the surface of nano grinding, but the surface of CMG is smooth without grinding traces and surface damage. Dong et al [31] used a CMG wheel of magnesium oxide (MgO) abrasives to grind silicon wafers.…”
Section: Introductionmentioning
confidence: 99%